1996
DOI: 10.1111/j.1365-2672.1996.tb01942.x
|View full text |Cite
|
Sign up to set email alerts
|

Colonization by lactobacilli of piglet small intestinal mucus

Abstract: The colonization potential of lactobacilli was investigated using small intestinal mucus extracts from 35‐d‐old pigs. Mucus‐secreting tissue from the small intestine of piglets was gently rinsed to remove contents and then shaken in buffer to release mucus from the surface. Numbers of lactobacilli in different portions of the small intestine of 35‐d‐old pigs were enumerated. Also, mucus isolated from the small intestine of pigs was investigated for its capacity to support the growth of lactobacilli. Results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 32 publications
4
17
0
Order By: Relevance
“…This strain showed a high expression of genes involved in amino-sugar catabolism and in the tricarboxylic acid cycle. Moreover, these results are in accordance with those of Rojas and Conway (1996) who demonstrated that Lactobacillus strains are able to utilise the small intestinal mucus for growth. Ability to develop in high number in intestinal mucus could represent an advantage for potential coloniser bacteria but also for potential probiotic Lactobacillus.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…This strain showed a high expression of genes involved in amino-sugar catabolism and in the tricarboxylic acid cycle. Moreover, these results are in accordance with those of Rojas and Conway (1996) who demonstrated that Lactobacillus strains are able to utilise the small intestinal mucus for growth. Ability to develop in high number in intestinal mucus could represent an advantage for potential coloniser bacteria but also for potential probiotic Lactobacillus.…”
Section: Resultssupporting
confidence: 92%
“…All strains showed a bacillary morphology, a Gram positive staining and a catalase negative reaction. Lactobacillus strains were found at similar levels to the previously reported (Rojas and Conway, 1996). These results indicate that even pigs that inhabit extreme conditions in arid coasts, maintain the levels of cultivable Lactobacillus strains in faeces and intestinal mucus.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…We chose a 4 h scale on the basis of the previous studies that demonstrated changes of metabolism and proteins in bacteria in response to a hostbacterium interaction [12,13]. In addition, we decided to place the chosen number of the Lactobacillus cells into the jejunum in light of the composition of microbiota in the pig small intestine [15,16]. Also, Lactobacilli at the mid-logphase were normally used in studies because they were more responsive to a treatment [13,17].…”
Section: Rabbit Model Of Intrajejunal Culture Of L Fermentum I5007mentioning
confidence: 99%